Improving IT Assessment with IT Artifact Affordance Perception Priming - Curry,Michael; Marshall,Byron; Kawalek,Peter (International Journal of Accounting Information Systems, 2015)
Accurately assessing organizational information technology (IT) is important for accounting professionals, but also difficult. Both auditors and the professionals from whom they gather data are expected to make nuanced judgments regarding the adequacy and effectiveness of controls that protect key systems. IT artifacts (policies, procedures, and systems) are assessed in an audit because they “afford” relevant action possibilities but perception preferences shade the results of even systematic and well-tested assessment tools. This study of 246 business students makes two important contributions. First we demonstrate that a tendency to focus on either artifact or organizational imperative systematically reduces the power of well-regarded IT measurements. Second, we demonstrate that priming is an effective intervention strategy to increase the predictive power of constructs from the familiar technology acceptance model (TAM).
Keywords: Accounting; BIS

IT Artifact Bias: How exogenous predilections influence organizational information system paradigms - Curry,Michael; Marshall,Byron; Kawalek,Peter (International Journal of Information Management, 2014)
Efforts in IS research have long sought to bridge the gap between the information technology (IT) function and strategic business interests. Efforts in IS research have long sought to bridge the gap between the information technology (IT) function and the strategic business interests. People perceive affordances (possibilities for action) in information technology artifacts differently as cognitive structures (schema) which bias individual focus. This study explores how an individual’s tendency to perceive the ‘trees’ in an IT ‘forest’ (artifact preference), affects their assessment of efforts to achieve more effective IT outcomes. The effect is demonstrated using a relatively simple IT success model. Further, in a sample of 120 survey responses supported by ten semi-structured interviews we demonstrate that job role and organizational IT complexity systematically impact artifact perception. A better understanding of IT artifact bias promises to help organizations better assess information systems.
Keywords: Accounting; BIS